Implementasi Low Power pada Monitoring Gas Berbahaya untuk Kandang Ayam dengan menggunakan Protokol HTTP dan ESP8266 - Frans Muliawan Panjaya; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The more number of chickens can make a very negative impact because of the increasing number of chicken manure in the cage. Chicken manure that is stacked in large quantities in a cage will produce a variety of harmful gases. If harmful gases arising from chicken coops exposed directly to humans will cause directly to the parts of organs in the body and respiratory problems. With the presence of a dangerous gas system in chicken coops, high risk can be prevented and used more easily in anticipating it. To be efficient in running system devices, the device in designing the system will utilize low power work for savings in power consumption. Power efficiency is carried out for battery energy sources used in the device to work in a relatively long period of time. The use of a low power system in Arduino Uno to implement devices on power consumption that is used more efficiently will not run out quickly. Sleep power down mode is used as a feature in this low power so that some sub-systems in the monitoring system of dangerous gas exposure in the chicken coop can be temporarily turned off. The resulting test is in the conclusion that the system can run as desired. Tested with MQ-4 and MQ-135 sensors there is a reading of the detected gas value with the value in the sensor. In testing low power power consumption on a device capable of suppressing currents of 11 to 12 mA from 183.95 mA with normal conditions or wake mode.